La Chiesa Ortodossa Russa e le riforme dell’inizio del XX secolo (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. La riforma di Pietro il Grande e la paralisi della Chiesa - 2. La diffusa aspirazione a ridefinire i rapporti tra Stato e Chiesa - 3. Verso il superamento dell’intolleranza religiosa - 4. Le prese di posizione di Antonij (Vadkovskij) e di Sergej Witte - 5. La reazione del Pobedonoscev – 6. Il Memorandum dei 32 - 7. Il riconoscimento della tolleranza religiosa - 8. I vescovi e la riforma ecclesiastica - 9. Il Manifesto del 17 ottobre e i ritardi nella convocazione del Concilio.The Russian Orthodox Church at the Beginning of the 20th CenturyABSTRACT: Peter the Great abolished the Patriarchate and entrusted the direction of the Church to a Holy Synod led by a laymen (Ober-prokuror). This reform had the consequence to paralyze the Church, as pointed out by F.M. Dostoevskij and by several outstanding Russian scholars. At the end of the 19th and at the beginning of the 20th century the necessity to overcome the relationship of subjection of the Church to the State was clearly perceived both by the intellectuals and inside the Church. The Tsar himself realized that there was a need of a change: the Fundamental laws were consequently modified and religious tolerance was acknowledged on April 17th 1905. Of paramount importance was the role played by the Prime-minister Sergej Witte and by the Metropolitan of St. Petersburg Antonij (Vadkovskij) to overcome the conservative ecclesiastical policy carried out by the Ober-prokuror Konstantin Pobedonoscev. The answers given by the bishops to a questionnaire issued by the Holy Synod on July 27th, 1905, confirmed that the problem was clearly felt also inside the Church. The Council of the Russian Church, which was supposed to be gathered at the beginning of the century, was summoned several years later, at the eve of the bolshevik coup d’état.